Novel application of phase change in thermal management of power electronics - Chen, Yiyi (2020)
Thermal management is a crucial step in the design of almost all industries such as renewable energies, processors, space, transportation, food and beverage industries. It involves controlling the temperature by means of heat transfer, conduction, convection, radiation and transfer of energy by phase changes, etc. In the automotive applications, the insulated gate bipolar transistor (IGBT) power module is one of the most important components in the power supply and motor control circuits in hybrid electric vehicles (HEV) and electric vehicles (EV). Nowadays, the heat dissipation density of IGBT is continuously increasing due to power rating improvements and miniaturisation. Without suitable cooling technologies, excessively high temperature and uneven temperature distribution can cause high thermal stress, eventually leading to severe module failures such as solder-ceramic delamination and crack as well as bonding wire lifts off. Therefore, highly efficient and compact cooling solutions are required. In thermal management design, boiling processes are very widely applied in many technical applications such as cooling technology, the chemical industry, power plant technology, refrigeration engineering, etc. To enhance boiling heat transfer, a pool boiling experiment was carried out. Copper surfaces with different channel sizes were used as boiling surfaces. Fe3O4 and polydimethylsiloxane (PDMS)-silica nanoparticles were used to be deposited on the surfaces. These two nanoparticles are able to modify the surface energy, which further causes changing in surface wettability. The surface contact angles become 14o and 145o after Fe3O4 and PDMS-silica nanoparticles were coated on surfaces, respectively. The maximum heat transfer coefficient found upon heterogeneous, hydrophobic and hydrophilic wetting surfaces are 81.5 kW/m2K, 77.4 kW/m2K, 50.4 kW/m2K, respectively, which are much higher than the 32.2 kW/m2K of the plain copper surface. To present a better understanding of the boiling enhancement mechanism of heterogeneous wetting channel surfaces, high-speed visualisations were used to observe bubble dynamics including nucleate site density, bubble departure diameter, bubble growth rate. Also, an experimental investigation was carried out to investigate the effect of channel width on boiling heat transfer of the heterogeneous wetting surface. Four channel widths-600 µm, 1000 µm, 2000 µm, and 2500 µm were selected. The heat transfer coefficient of 110.3 kW/m2K was obtained on the heterogeneous wetting surface with channel width of 600 µm. The enhancement ratio of heat transfer coefficient reached up to 35 %, 39 %, 45 % and 242 % compared with the surface with channel width of 1000 µm, 2000 µm, 2500 µm, and plain copper surface. This enhancement was mainly attributed to the increase the actural surface area, capillary-assisted suction ability, hydrophobic area percentage and reducing bubble base diameter. In application of phase change in thermal management of power electronics, the aim is to develop a cooling solution to quickly transfer high heat flux and reduce the temperature gradient of the IGBT power module. The cooling solution based on vapour chamber in which phase change directly takes place was developed and analysed. The experiments and simulation confirmed that both the thermal and thermo-mechanical performances of IGBT with the novel designed are better than that of the IGBT with copper baseplate module. The experiment mainly analysed temperature distribution in layers, junction temperature, temperature uniformity and thermal resistance. The simulation study focused on thermo-mechanical performances of IGBT such as thermal stress, deformation, creep and plastic strain energy dissipation and predicting thermal fatigue life. It also studied the failure mechanism under power cycling